Communist Manifesto and The Peasantry Of The 21st Century - Šljukić, Srđan Lj.; Šljukić, Marica N. (Sociološki pregled, 2018)
A hundred and seventy years ago in Communist Manifesto K. Marx and F. Engels gave several prognoses regarding the future changes of the social structure. According to one of them, peasantry was sentenced to disappearing, by the laws of capitalism. Since this prediction has been written, in the large part of the world the process of deagrarization has taken place, together with industrialization of agricultural production. However, peasantry did not disappear; on the contrary, it reappeared in some countries. The explanation of these contradictory processes we fnd the theory or repeasantization, given by a Dutch sociologist J. D. van der Ploeg. The same social forces that cause depeasantization, like modernization, industrialization and globalization, provoke the resistance of farmers and their struggle for autonomy. Tis struggle can be recognized in the comeback of the peasant mechanisms in the agricultural production.Keywords: Communist Manifesto, depeasantization, globalization, industrialization of agriculture, modernization, repeasantization, peasantry.